2020
DOI: 10.1155/2020/8581202
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Bank Operational Efficiency Using Machine Learning Algorithm: Comparative Study of Decision Tree, Random Forest, and Neural Networks

Abstract: The financial crisis that hit Ghana from 2015 to 2018 has raised various issues with respect to the efficiency of banks and the safety of depositors’ in the banking industry. As part of measures to improve the banking sector and also restore customers’ confidence, efficiency and performance analysis in the banking industry has become a hot issue. This is because stakeholders have to detect the underlying causes of inefficiencies within the banking industry. Nonparametric methods such as Data Envelopment Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…They utilize ML methods for identifying the synthetic feature of the networks. Appiahene et al ( 2020 ) presented an integrated DEA using 3 ML methods in calculating bank performance and efficiency with 444 Ghanaian bank branches, DMUs. The outcomes are related to the respective efficacy rating attained from the DEA.…”
Section: Related Workmentioning
confidence: 99%
“…They utilize ML methods for identifying the synthetic feature of the networks. Appiahene et al ( 2020 ) presented an integrated DEA using 3 ML methods in calculating bank performance and efficiency with 444 Ghanaian bank branches, DMUs. The outcomes are related to the respective efficacy rating attained from the DEA.…”
Section: Related Workmentioning
confidence: 99%
“…In a study by Appiahene et al [9], whether the Z-score model can effectively determine the financial crisis of listed enterprises in China was investigated, and the results showed that the Z-score model has an outstanding prediction effect for certain types of enterprises. In 2015, Fabling and Grimes [10] established a multivariate probability ratio regression model in conducting a study on financial crisis prediction.…”
Section: Related Workmentioning
confidence: 99%
“…According to a citation by (Appiahene et al, 2020), an artificial neural network (ANN) is a sort of Artificial Intelligence (AI) technique that mimics the behavior of a human brain. Artificial Neural Networks (ANN) are a data processing model based on how the biological nervous system, such as the brain, processes information.…”
Section: The Artificial Neural Networkmentioning
confidence: 99%
“…Figure 2: The proposed model (Source: Author's own)3.2.1 Random Forest (RF) AlgorithmBreiman in 2001 and cited by(Appiahene et al, 2020) said the Random Forest (RF) algorithm is used for classification and prediction that employs an ensemble of classification trees. Random Forest is a learning method that entails the construction of many decision trees.…”
mentioning
confidence: 99%